2016
DOI: 10.1063/1.4960638
|View full text |Cite
|
Sign up to set email alerts
|

Charge transport model in nanodielectric composites based on quantum tunneling mechanism and dual-level traps

Abstract: Charge transport properties in nanodielectrics present different tendencies for different loading concentrations. The exact mechanisms that are responsible for charge transport in nanodielectrics are not detailed, especially for high loading concentration. A charge transport model in nanodielectrics has been proposed based on quantum tunneling mechanism and dual-level traps. In the model, the thermally assisted hopping (TAH) process for the shallow traps and the tunnelling process for the deep traps are consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…Conversely, for higher loading ratio nanocomposites, higher than 5 wt% as results presented in this research and similar work reported in [38,39], the short separation distance due to the increased number of deep traps as shown in Fig. 9 (b) prompts the tunnelling process to dominate the transport of charge carriers to the adjacent traps in contrast to overcoming the energy barrier [26]. Consequently, the captured charges are able to escape from the traps located near the subsurface and continue to transport through the bulk, and charge carriers can continue to be injected into the nanocomposites as opposite field at the interface becomes low.…”
Section: Discussion With Tunneling Modelsupporting
confidence: 85%
“…Conversely, for higher loading ratio nanocomposites, higher than 5 wt% as results presented in this research and similar work reported in [38,39], the short separation distance due to the increased number of deep traps as shown in Fig. 9 (b) prompts the tunnelling process to dominate the transport of charge carriers to the adjacent traps in contrast to overcoming the energy barrier [26]. Consequently, the captured charges are able to escape from the traps located near the subsurface and continue to transport through the bulk, and charge carriers can continue to be injected into the nanocomposites as opposite field at the interface becomes low.…”
Section: Discussion With Tunneling Modelsupporting
confidence: 85%
“…It is obvious, in the case of the hopping process, the mobility of charges is inversely proportional to the inter-trap distance. Moreover, in some previous research, tunnelling process is also suggested to explain charge transport in polymer nanocomposites with higher filler ratios [13,39]. There provides a good way to understand the suppressed charge transport in samples of low filler loading ratios and increased charge dynamics in that of high ratios.…”
Section: Discussionmentioning
confidence: 97%
“…the bulk with the growth of filler loading ratios. Moreover, EPB samples clearly show suppressed injection when compared to silica-based ones and an increase in initial builtup charge with the growth of filler loadings, which may refer to the presence of shallow traps in bulk [13] due to the morphology in bulk.…”
Section: Space Chargementioning
confidence: 98%
“…Furthermore, when applied V G is greater than V TH , silicon bands bend more upward as shown in Figure 6d, and current conduction is governed by interface‐trap assisted tunneling (blue arrow) at low electric fields and partial F‐N tunneling (green arrow) at high fields as discussed in Figure 6b. Trap assisted tunneling is aid by low energy electrons tunneling to the intermediate interface, border/shallow traps, bulk/deep‐level traps [ 70 ] , and corresponding triangular barrier. However, F‐N tunneling is aid by electrons that have sufficient energy to directly overcome the triangular barrier.…”
Section: Resultsmentioning
confidence: 99%